2022
DOI: 10.1039/d1qo01662h
|View full text |Cite
|
Sign up to set email alerts
|

Visible light promoted polyhalomethylation of alkenes: alkylation and cyclization

Abstract: We report a visible light promoted carbochloromethylation of 2-bromomethyl acrylate and N-arylmethacrylamide, and a series of trihalomethyl substituted allylic acid esters and indolone derivatives were synthesized. The reaction used common...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…S9 and S10†). As a result, neither the ground-state nor photoexcited eosin Y would be preferentially oxidized at the anode, excluding both the electron-primed photocatalytic mechanism 19,21 a , b ,22 and oxidative quenching cycle 32 -involved electrophotocatalytic pathway. It is established that 2a could significantly attenuate eosin Y fluorescence in a Stern–Volmer quenching experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9 and S10†). As a result, neither the ground-state nor photoexcited eosin Y would be preferentially oxidized at the anode, excluding both the electron-primed photocatalytic mechanism 19,21 a , b ,22 and oxidative quenching cycle 32 -involved electrophotocatalytic pathway. It is established that 2a could significantly attenuate eosin Y fluorescence in a Stern–Volmer quenching experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eosin Y is a versatile photosensitizer, 31 and while it is a frequently used photoreductant, 32 it could function as a photooxidant as well. 33,34 Cyclic voltammetry (CV) tests indicated that eosin Y has an oxidation potential of 1.00 V vs. Ag/AgCl (Scheme 3d and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it can also serve as a flexible precursor for various halogenated groups in organic synthesis. Chloroform selectively produces trichloromethyl radicals in the presence of peroxides, [12] copper catalysts, [13] or photocatalysts [14] . Subsequent studies have found that chloroform can also selectively produce dichloromethyl radicals under appropriate conditions [15] .…”
Section: Methodsmentioning
confidence: 99%
“…ces trichloromethyl radicals in the presence of peroxides, [12] copper catalysts, [13] or photocatalysts. [14] Subsequent studies have found that chloroform can also selectively produce dichloromethyl radicals under appropriate conditions. [15] For example, the Doyle research group utilized copper catalysis to achieve the alkylation peroxidation of olefin with TBHP and CHCl 3 to efficiently construct various α-tert butyl peroxide-β-dichloromethyl substituted alkanes.…”
mentioning
confidence: 99%
“…Distinctive polychloromethylated molecules containing di- or trichloromethyl moieties are significant subclasses that are widely found in pharmaceuticals, pesticide molecules, and biologically active natural products. 1 Among them, the polychloromethyl moiety is usually the critical functional unit for providing effective activity. Given the importance of polychloromethyl compounds, chemists have developed several approaches for realizing polychloromethylation, including the use of novel halogenating enzymes to catalyze the polychloromethylation of unactivated aliphatic carbon centers, 2 peroxide-induced halogenated addition to alkenes, 3 the nucleophilic addition of chloroform or dichloromethane to alkenes in the presence of strong bases, 4 and so on.…”
mentioning
confidence: 99%